Reversible Diels–Alder Addition to Fullerenes: A Study of Dimethylanthracene with H2@C60 - Mahboob Subhani; Jinrong Zhou; Yuguang Sui; Huijing Zou; Michael Frunzi; James Cross; Martin Saunders; Cijun Shuai; Wenjie Liang; Hai Xu (Nanomaterials, 2022)
The study of isolated atoms or molecules inside a fullerene cavity provides a unique environment. It is likely to control the outer carbon cage and study the isolated species when molecules or atoms are trapped inside a fullerene. We report the Diels–Alder addition reaction of 9,10-dimethyl anthracene (DMA) to H2@C60 while 1H NMR spectroscopy is utilized to characterize the Diels–Alder reaction of the DMA with the fullerene. Through 1H NMR spectroscopy, a series of isomeric adducts are identified. The obtained peaks are sharp, precise, and straightforward. Moreover, in this paper, H2@C60 and its isomers are described for the first time.